2009
DOI: 10.1111/j.1551-2916.2009.03133.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinel‐Coated Graphite for Carbon Containing Refractory Castables

Abstract: Oxidation resistance and water wettability of graphite flakes have been improved by a thin sol–gel film of magnesium aluminate spinel (MgAl2O4) over its surface. The hydrosol has been synthesized by less expensive precursors and the spinel formation has been studied by scanning electron microscopy (SEM), supplemented with energy dispersive spectral analysis. After an easy‐to‐use mixing procedure, drying (110°C), and subsequent calcination (550°C), coated graphites were sieved to below 75 μm. The coating over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
5
32
0
Order By: Relevance
“…5a(i)) represents the overall /average composition of graphite surface. Ca, Al, Si all are observed due to both calcium aluminate coating and alumino silicate ash/clayey impurities inherently present on to graphite flakes [15]. The second adjacent plot (Fig.…”
Section: Characteristics Of Calcium Aluminate-coated Graphite and Resmentioning
confidence: 94%
See 2 more Smart Citations
“…5a(i)) represents the overall /average composition of graphite surface. Ca, Al, Si all are observed due to both calcium aluminate coating and alumino silicate ash/clayey impurities inherently present on to graphite flakes [15]. The second adjacent plot (Fig.…”
Section: Characteristics Of Calcium Aluminate-coated Graphite and Resmentioning
confidence: 94%
“…The refractory castables preparation has also been elaborately discussed in our previous contributions [15][16][17]. It was a low cement (4.0 mass%) batch containing white fused alumina(WFA) aggregates (72.0%) in several size fractions, e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A secondary problem of atmospheric pollution arises due to emission of carbon monoxide (CO) and/or carbon dioxide (CO 2 ) gases because of prevailing oxidizing atmosphere at the application site. Surface modification of graphite has thus been adopted by many researchers with a desire to reduce water content of batch and minimize rate of emission of carbonaceous products by environmentally benign manner [5,6,7]. The use of novel forms of carbon materials e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this pursuit of achieving high‐tech and heavy‐duty ceramic‐carbon monoliths for steel plants, our ideal choice was to develop coated graphite by sol‐gel route. Taking the clue that hydrophilic thin film on graphite can assist fabrication and carbon protection, a cost‐competent nanostructured ceramic oxide coated graphite for monolithic refractories has already been reported . Our preliminary observations revealed that this coating behaved as an intermediate bridging link between the castable and graphite that upgraded the performance of alumina based refractory.…”
Section: Introductionmentioning
confidence: 72%